Experiences of Children with Fetal Alcohol Spectrum Disorder and Their Families: A Critical Review. (6th May 2020) - Skorka, Kelly; McBryde, Catherine; Copley, Jodie; Meredith, Pamela J.; Reid, Natasha
Abstract : Evidence suggests that children with fetal alcohol spectrum disorder (FASD) experience challenges across many areas of their daily lives and often require interprofessional supports. Recent studies have emphasized the need for an integrated system of care for children with FASD, incorporating medical, allied health, and education services, to facilitate open communication and support for the complex needs that many children experience. To develop such a system of care, it is important to first understand the impact of FASD on children's functioning during daily activities in different environmental contexts. A critical review of existing research was conducted using a critical interpretive synthesis approach. Results revealed that while many studies discussed impacts at the body functions and structures level of children with FASD, they often did not consider the activity, participation, and environmental factors also contributing to the daily functioning of this population. Several studies discussed caregiver experiences and challenges raising a child with FASD; however, no studies investigated the lived experiences relating to impacts across activities and environments from children's perspectives. In addition, the focus on deficits overshadowed investigation into the strengths of children with FASD, leaving a gap in the picture of their daily lives. Further research is required to determine the strengths that children with FASD demonstrate and the challenges impacting their daily functioning within different environmental contexts. Insights gleaned from such research would support intervention practices to become more holistic and interprofessional. Abstract : A critical review of the literature documenting the impacts of FASD on children's functioning revealed that while the impairments experienced by children are well documented, there is a lack of clarity regarding how these impairments impact on performance of their daily activities. In addition, little is known about strengths and the lived experiences of those with FASD. Further understanding in these areas has the potential to inform more holistic inter‐professional, context‐focused approaches that are truly strengths‐based and client‐centred.